Impact of the North-East Line (NEL) on tourism in Singapore. - Liew, Hung Wai. (2008)
The objective of the research is to examine the effects the NEL has on tourism in Singapore, how it has benefited tourism in the country. This study hopes to identify the critical variables considered by tourists when they take public transport in a foreign country. The research also aims to obtain information on how the NEL has impacted business in the tourist-concentrated areas mentioned.